PENGENALAN PEMBUKUAN KEUANGAN DILINGKUNGAN KELUARGA SEBAGAI SALAH SATU KUNCI KEHARMONISAN RUMAH TANGGA DI DESA KP. BARU, PAMARAYAN - Raden Irna Afriani; Ade Samsinar; Rika Kartika; Nindi Yuliyanti; Dian Ayu Safitri; Citra Wati (Yayasan Education and Social Center, 2022)
Poor financial management among families has caused many problems. The main problem is the destruction of the household ark. Therefore, to prevent the increasing number of divorce rates, the service team took the initiative to conduct counseling on the introduction of financial bookkeeping in the family environment. With the aim that after this counseling was held, housewives as